Diagnosis and management of acute acalculous cholecystitis in an outpatient: a case report - Arockia Singh, Maria Dass Scott; Anish Kumar, Meethala Peedikayil (International Surgery Journal, 2019)
Acute acalculous cholecystitis (AAC) is defined as acute necrotic inflammation of the gall bladder without stone disease. It commonly occurs in ICU patients associated with major trauma, burns, multiorgan failure patients, post major surgery, end stage malignancies, severe sepsis. Here we present a case of acute acalculous cholecystitis with gangrenous formation in a middle-aged outpatient without any prior illness. He was a hypertensive on medications came with complains of abdominal pain. Clinical examination and ultrasound revealed features suggestive of infective acalculous gall bladder disease. Emergency laparoscopic subtotal cholecystectomy done, discharged in a healthy state on 3rd postoperative day. We present this case to raise awareness among primary care physicians of AAC in patients with acute right hypochondrial pain. Prompt diagnosis and urgent surgical management gives the best outcome in these patients.